ALOKASI ANGGARAN KESEHATAN TERHADAP ANGKA HARAPA HIDUP MASYARAKAT MASYARAKAT DI KALIMANTAN BARAT - B01109015, Trida Marsaulina (Jurnal Pembangunan dan Pemerataan, 2015)
This Study is titled â€œHealth Budget Allocation against Life Expectancy in West Borneoâ€ aims to identify and analize the influence of Health Budget Allocation against the Life Expectancy of society in West Borneo. The method of analysis used in this study is regression using Pooled Data tosee theeffect of government spendingon health sector against Life ExpectancyÂ  in regency/city in West Borneo from 2009 until 2011. Testing includes statistical tests. The result of the data analysis showed that Health Budget simultaneously influence significantly and positively to the Life Expectancy in West Borneo. It also partially influence significantly and positively to the Life Expectancy in West Borneo. Whereas the Coefficient of Determination (R2) showed that the value of R2is 11,8175%, and the rest is influenced by other variables outside the model under study. Keywords: Life Expectancy and Health Budget